Frequent Emergency Department Utilization and Behavioral Health Diagnoses. Issue 1 (January 2015) - Castner, Jessica; Wu, Yow-Wu B.; Mehrok, Navinder; Gadre, Angad; Hewner, Sharon
<x xml:space="preserve">Abstract</x> Background There are 12 million emergency department (ED) visits each year related to behavioral health diagnoses. Frequent ED utilization among subpopulations, such as those with behavioral health diagnoses, flags the need for more accessible and effective healthcare delivery systems. Reducing frequent ED use is essential to controlling healthcare cost and poor outcomes of ED overcrowding. Objectives The purpose of this study is to stratify individuals by overall health complexity and examine the relationship of behavioral health diagnoses (psychiatric and substance abuse) as well as frequent treat-and-release ED utilization in a cohort of Medicaid recipients. Methods This study was a retrospective analysis of 2009 Medicaid claims from two Western New York State counties. The claims represented 56, 491 individuals (18–64 years old). Individuals were stratified into four separate cohorts for analysis based on underlying disease complexity. Data were analyzed using logistic regression models. Results The following factors significantly increased the odds of frequent treat-and-release ED use in all the four complexity cohorts: psychiatric diagnosis (ORs = 1.4–2.3), substance abuse (ORs = 2.4–3.8), and smoking (ORs = 1.7–4.0). Medicaid patients with behavioral health diagnoses show high risk of frequent treat-and-release ED use. Discussion The results of this study show that psychiatric diagnosis, substance abuse, and smoking are associated with increased odds of frequent treat-and-release ED utilization for Medicaid recipients in all categories of underlying disease complexity. Our findings support associations reported in the literature.